An Exploration of the Transformation of the 8‐Oxo‐7, 8‐Dihydroguanine Radical Cation to Protonated 2‐Amino‐5‐Hydroxy‐7, 9‐Dihydropurine‐6, 8‐Dione in a Base Pair. Issue 3 (27th October 2022) - Wei, Simin; He, Qihao; Duan, Jinwei; Zheng, Huayu; Ma, Lei; Wang, Yinghui
Abstract: A theoretical investigation was performed to disclose the transformation mechanism of 8‐oxo‐7, 8‐dihydroguanine radical cation (8‐oxoG⋅ + ) to protonated 2‐amino‐5‐hydroxy‐7, 9‐dihydropurine‐6, 8‐dione (5‐OH‐8‐oxoG) in base pair. The energy profiles for three possible pathways of the events were mapped. It is shown that direct loss of H7 from base paired 8‐oxoG⋅ + is the only energetically favorable pathway to generate neutral radical, 8‐oxoG(‐H7)⋅. Further oxidation of 8‐oxoG(‐H7)⋅ : C to 8‐oxoG(‐H7) + : C is exothermic. However, the 8‐oxoG(‐H7) + : C deprotonation from all possible active sites is infeasible, indicating the inaccessible second proton loss and the lack of essential intermediate 2‐amino‐7, 9‐dihydropurine‐6, 8‐dione (8‐oxoG OX ). This makes 8‐oxoG(‐H7) + act as the precursor of hydration leading to the generation of protonated 5‐HO‐8‐oxoG by stepwise fashion in base pair, which would initiate the step down guanidinohydantoin (Gh) pathway. These results clearly specify the structure‐dependent transformation for 8‐oxoG⋅ + and verify the emergence of protonated 5‐HO‐8‐oxoG in base pair. Abstract : Transformation mechanisms for 8‐oxoG ⋅ + in base pair are investigated by density functional calculations. The results distinctly specify the structure‐dependent degradation of 8‐oxoG⋅ + and verify the emergence of protonated 5‐HO‐8‐oxoG in base pair after oxidizing 8‐oxoG by extracting electrons.